2015
DOI: 10.1021/acs.analchem.5b01833
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Multistep Immobilized Metal Affinity Chromatography and Multistep TiO2 Methods for Phosphopeptide Enrichment

Abstract: Phosphopeptide enrichment from complicated peptide mixtures is an essential step for mass spectrometry-based phosphoproteomic studies to reduce sample complexity and ionization suppression effects. Typical methods for enriching phosphopeptides include immobilized metal affinity chromatography (IMAC) or titanium dioxide (TiO2) beads, which have selective affinity and can interact with phosphopeptides. In this study, the IMAC enrichment method was compared with the TiO2 enrichment method, using a multi-step enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 27 publications
3
65
1
1
Order By: Relevance
“…Our previous work demonstrated that multiple rounds of enrichment, performed sequentially, provided efficient enrichment and recovery of phosphopeptides [15, 16],. Three rounds of IMAC enrichment yielded 4,331 phosphopeptides, 30% of the total identifications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous work demonstrated that multiple rounds of enrichment, performed sequentially, provided efficient enrichment and recovery of phosphopeptides [15, 16],. Three rounds of IMAC enrichment yielded 4,331 phosphopeptides, 30% of the total identifications.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphopeptides were enriched using both IMAC and TiO 2 beads to enhance coverage, since the two chemistries have been reported to enrich complementary sub-proteomes [14, 15]. Digests were performed in triplicate on two occasions, once for each enrichment method.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…51 For example, Fe 3+ and Ga 3+ -based IMAC strategies are often biased toward enrichment of multiply phosphorylated peptides, while TiO 2 -based chromatography is typically biased toward mono-phosphorylated peptides. 49, 52, 53 Physiological loading buffers such as PBS and certain additives to prevent non-specific binding of acidic peptides (e.g. citric acid) have also been shown to bias enrichments toward multiply phosphorylated peptides, presumably because peptides with several phosphorylation groups have stronger metal ion affinity.…”
Section: Enrichment Techniquesmentioning
confidence: 99%